1999
DOI: 10.1073/pnas.96.23.13496
|View full text |Cite
|
Sign up to set email alerts
|

A tetracycline derivative, minocycline, reduces inflammation and protects against focal cerebral ischemia with a wide therapeutic window

Abstract: The only treatment of patients with acute ischemic stroke is thrombolytic therapy, which benefits only a fraction of stroke patients. Both human and experimental studies indicate that ischemic stroke involves secondary inflammation that significantly contributes to the outcome after ischemic insult. Minocycline is a semisynthetic second-generation tetracycline that exerts antiinflammatory effects that are completely separate from its antimicrobial action. Because tetracycline treatment is clinically well toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

40
755
2
10

Year Published

2002
2002
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 958 publications
(811 citation statements)
references
References 32 publications
40
755
2
10
Order By: Relevance
“…In animals, minocycline is lethal at very high doses (LD 50 :3600 mg/kg; Blum et al, 2004;Smith et al, 2003). In humans, long-term treatment with minocycline up to 200 mg/day is generally safe and well tolerated as In recent years, minocycline has been reported to have neuroprotective effects in various experimental neurodegenerative disease models such as cerebral ischemia (Yrjanheikki et al, 1999), traumatic brain injury (Sanchez Mejia et al, 2001), ALS (Zhu et al, 2002), PD (Wu et al, 2002), and HD (Chen et al, 2000;Wang et al, 2003). At present, a few number of studies are focused on the therapeutical potential of minocycline in AD (Hunter et al, 2004a;Seabrook et al, 2006), where it suppressed microglial production of IL-1beta, IL-6, TNF, and NGF in in vitro as well as APP transgenic mice (Seabrook et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals, minocycline is lethal at very high doses (LD 50 :3600 mg/kg; Blum et al, 2004;Smith et al, 2003). In humans, long-term treatment with minocycline up to 200 mg/day is generally safe and well tolerated as In recent years, minocycline has been reported to have neuroprotective effects in various experimental neurodegenerative disease models such as cerebral ischemia (Yrjanheikki et al, 1999), traumatic brain injury (Sanchez Mejia et al, 2001), ALS (Zhu et al, 2002), PD (Wu et al, 2002), and HD (Chen et al, 2000;Wang et al, 2003). At present, a few number of studies are focused on the therapeutical potential of minocycline in AD (Hunter et al, 2004a;Seabrook et al, 2006), where it suppressed microglial production of IL-1beta, IL-6, TNF, and NGF in in vitro as well as APP transgenic mice (Seabrook et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its antibiotic properties, minocycline has been reported to have neuroprotective effects in various experimental models of cerebral ischemia (Yrjanheikki et al, 1999), traumatic brain injury (Sanchez Mejia et al, 2001), amyotrophic lateral sclerosis (ALS) (Zhu et al, 2002), Parkinson's diseases (PD) (Wu et al, 2002), kainic acid treatment (Heo et al, 2006), Huntington's disease (HD) (Chen et al, 2000;Wang et al, 2003), and multiple sclerosis (Popovic et al, 2002). Additionally, minocycline was reported to attenuate white matter damage in a rat model of chronic cerebral hypoperfusion .…”
Section: Introductionmentioning
confidence: 99%
“…A similar long therapeutic time window in brain ischemia has been reported for other pharmacological strategies aimed at reducing post-ischemic inflammation (Iadecola et al, 1995;Nagayama et al, 1998;Cash et al, 2001). In addition, several studies have found neuroprotective effects of different compounds when administered after ischemia (Jiang et al, 1998;Yrjanheikki et al, 1999;Haag et al, 2000;Phillips et al, 2000;Zhang et al, 2001;Snider et al, 2001;Lavie et al, 2001;Mary et al, 2001), suggesting that brain injury produced by cerebral ischemia develops over a period of hours to days after the primary event.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline was shown to suppress microglial activation and improve neuronal survival after brain ischemia. 228,229 Minocycline and other PARP-1 inhibitors are entering clinical trials for treatment of stroke and other conditions. 230 -232 …”
Section: Other Factors That Influence Proinflammatory Gene Transcriptionmentioning
confidence: 99%